2019
DOI: 10.3389/fnmol.2019.00019
|View full text |Cite
|
Sign up to set email alerts
|

Neurocalcin Delta Knockout Impairs Adult Neurogenesis Whereas Half Reduction Is Not Pathological

Abstract: Neurocalcin delta (NCALD) is a brain-enriched neuronal calcium sensor and its reduction acts protective against spinal muscular atrophy (SMA). However, the physiological function of NCALD and implications of NCALD reduction are still elusive. Here, we analyzed the ubiquitous Ncald knockout in homozygous ( Ncald KO/KO ) and heterozygous ( Ncald KO/WT ) mice to unravel the physiological role of NCALD in the brain and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…In AD, the GABA signaling system is dysregulated with changes in GABA expression in the hippocampus (Calvo-Flores Guzmán et al, 2018). NCALD is a calcium sensor that is involved in neuronal calcium signaling (Stelzer et al, 2016; Upadhyay et al, 2019). NEFL makes the protein neurofilament light chain (Nfl), which has recently been investigated as a fluid biomarker for monitoring AD disease progression (Preische et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In AD, the GABA signaling system is dysregulated with changes in GABA expression in the hippocampus (Calvo-Flores Guzmán et al, 2018). NCALD is a calcium sensor that is involved in neuronal calcium signaling (Stelzer et al, 2016; Upadhyay et al, 2019). NEFL makes the protein neurofilament light chain (Nfl), which has recently been investigated as a fluid biomarker for monitoring AD disease progression (Preische et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressed Ncald induced a reduction in axon outgrowth and branching of cultured hippocampal neurons ( Yamatani et al ., 2010 ), and Ncald KO restored axonal growth in zebrafish and mice ( Riessland et al ., 2017 ). In contrast, Upadhyay et al . (2019) reported that Ncald KO impaired neurogenesis in adult mice, while Ncald heterozygous mice did not exhibit significant changes.…”
Section: Discussionmentioning
confidence: 84%
“…NCALD, AT2A2 (also known as SERCA2) and AT2B1 are play pivotal role in the calcium homeostasis. NCALD primarily involved in neuronal calcium signaling mechanism and it is speculated that there is a close relationship between NCAL and adult neurogenesis [23]. SERCA2 is an intracellular calcium pump on the endoplasmic or sarcoplasmic reticulum, plays an essential role in regulating calcium homeostasis [24,25].…”
Section: Discussionmentioning
confidence: 99%